(untitled) (Journal of International Crisis and Risk Communication Research, 2020)
In 2014, a water crisis emerged in Flint, Michigan. Using uses and gratifications theory as the guiding framework, this study examines if crisis-related media uses, informational needs, and source preferences are related to respondents’ gender and/or whether ornot respondents had children. A random sample of 208 Flint residents yielded results that are largely consistent with extant research, although minor nuances were found. Media uses, preferred informational sources, and desire to receive future crisis-related health information varied between women and men. Women reported significantly higher use of Facebook and Instagram. However, there were not significant differences between genders or respondents with/without children regarding their future informational needs about crisis-related health topics. Results are discussed in relation to extant research, theory, and praxis. Limitations and future research are also discussed.